2022
DOI: 10.1021/acsaelm.2c00195
|View full text |Cite
|
Sign up to set email alerts
|

Surface Passivation of III–V GaAs Nanopillars by Low-Frequency Plasma Deposition of Silicon Nitride for Active Nanophotonic Devices

Abstract: low frequency (380 kHz) excitation plasma that enable intense bombardment of hydrogen, all seem to provide a combined active role in the passivation mechanism of the pillars by reducing the surface states.As a result, we observe up to a 29-fold increase of the photoluminescence (PL) integrated intensity for the best samples as compared to untreated nanopillars. X-ray photoelectron spectroscopy analysis confirms the best treatments show remarkable removal of gallium and arsenic native oxides. Time-resolved micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The device performance can be further improved via surface passivation to reduce surface recombination velocity and increase the cavity Q. 38 ■ METHODS Device Fabrication. The devices are fabricated from an InP wafer, with 300 nm epitaxially grown InGaAsP MQW covered by a 10 nm InP overlayer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The device performance can be further improved via surface passivation to reduce surface recombination velocity and increase the cavity Q. 38 ■ METHODS Device Fabrication. The devices are fabricated from an InP wafer, with 300 nm epitaxially grown InGaAsP MQW covered by a 10 nm InP overlayer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our experimental results validate the expected device performance, showing a high Purcell factor of 74, which corresponds to a modulation bandwidth of 6.65 GHz. The device performance can be further improved via surface passivation to reduce surface recombination velocity and increase the cavity Q . This demonstration serves as a crucial prototype for fast and efficient nanoscale light sources, offering promising prospects for future high-speed optical interconnects.…”
Section: Discussionmentioning
confidence: 99%
“…The key neuron-like functions of this nanoRTD-LED emitter architecture was first proposed in [78]. In this Section, we summarize the main properties of the nanoLED neuron emitters, as well as recent advances reported elsewhere in realizing and improving such nanoemitters, namely increasing their output power enabled by light extraction [79], and surface passivation [80] methods.…”
Section: Nanoled Neuron Emitter: Nanortd-ledmentioning
confidence: 99%
“…Passivation of GaAs with silicon nitride (Si x N y ) has been proposed to improve GaAs electrical performance [87]. Recently, it has been demonstrated that surface passivation using a combination of ammonium sulphide chemical treatment followed by encapsulation with a thin layer of Si x N y (80 nm) deposited by low-frequency plasma enhanced chemical vapour deposition (LF-PECVD) can result in improved optical properties of nanopillar LEDs [80]. The results show that passivated GaAs nanopillar surfaces are robust, stable, and long-lasting.…”
Section: Nanoled Neuron Emitter: Nanortd-ledmentioning
confidence: 99%
See 1 more Smart Citation